Can the UAE Avoid the Oil Curse by Economic Diversification? - Ilham Haouas; Almas Heshmati (Institute for the Study of Labor (IZA), 2014)
Recent research conclude that the GCC economies have failed to address the oil curse. They are far behind other countries, especially those in the G7, which possess huge reserves of oil wealth but have undertaken economic diversification to correct the ill-effects of an oil curse. This paper takes an in-depth look into the UAE economy as a model but also as a reminder of the struggles ahead. The findings support the fact that the UAE is facing an oil curse. Declining levels of total factor productivity, GDP volatility, negative returns on investment, and a labor force that is too reliant on government's supply of jobs are among the many reasons that support the thesis. The UAE has made good progress in recent years to diversify its economy. However, the drivers of economic growth in the UAE are vulnerable to external shocks outside of the Emirate's control. It is now critical that the UAE take steps to mitigate economic disruptions that might result from these shocks. In this case study the UAE economic performance is examined, and a data-driven roadmap for sustainable growth is suggested. The analysis shows that greater efforts are needed to stimulate the diversification of the production base by encouraging increased domestic, especially private, investment. Well-targeted policies should be adopted to accelerate reform and facilitate the involvement of the private sector in the economy.
Keywords: C22; E20; L16; L71; O11; O53; 330; growth accounting; TFP; oil curse; economic diversification; UAE